The Relationship between Inadequate Teaching Method and Students’ English Learning Difficulties - Zahratul Fikni; Siti Maysuroh; Muhammad Aldi Soleh (Humanitatis : Journal of Language and Literature, 2023)
This research aimed to identify the relationship between inadequate teaching method and student’s English learning difficulties. This research used a quantitative descriptive approach. The data source was the students of the third grade of Junior High School 1 Pringgasela. The data were taken from the observation and questionnaire designed to identify the relationship between inadequate teaching method and student’s English learning difficulties that were shared to the population of the research comprising (90) male and female students to acquire the research objective. Through the finding of the analysis, there were collected about 200 responses from 10 numbers of statements each was answered by 20 students distributed as 10 males and 10 females selected from 90 students as the populations who were then displayed as respective percentage of 50% male and 50% female students. The questionnaire embodied several contexts such as curriculum, teaching method and student’s difficulties in learning English language. The results showed that 113 responses agreed with the statement given, while 87 statements disagreed. The number of responses was presented in terms of percentage as 57% of the respondents agreed while the remaining 43% disagreed. The broader findings will be further discussed.